The Implementation of Quizizz Application as a Learning Media in Teaching English in Senior High School - Elsi Suciati Berutul; Deasy Yunita Siregar (South Sulawesi Education Development (SSED), 2024)
In the era of revolution 4.0, technology plays an important role in every human life. It seems that in the world of education, technology has had quite a big impact on technological development, both negative and positive impacts. One of the positive impacts of technological developments in the education sector is that students and teachers can access information whenever and wherever they are. Apart from that, the use of technology can also be utilized in the teaching and learning process. Therefore, teachers are expected to be able to provide active and interactive learning using interesting and fun media such as PowerPoint, YouTube, and other media. One application that can be used is the Quizizz application. Quizizz is a web tool that contains interactive quizzes that are suitable for distance learning and face-to-face learning. The purpose of this research is to see an overview or explanation regarding the application of the Quizizz application in the classroom. This research uses descriptive qualitative research methods with several blood collection techniques such as observation, interviews, and documentation. The results of this research show that Quizizz has a quite good impact on classroom learning. This can be seen from the evaluation results of students who obtained an average score above the cut mark. So it can be concluded that the Quizizz media is very suitable and effective for use as an evaluation medium for both face-to-face and distance learning because it is not limited by space and time, making it easier for students and teachers.